Turnin' up voter turnout determining the impact of district representative candidates' campaign spending on voter turnout - Corpus, Jillian Victoria D.; Pacana, Celina Me'shell F.; Daway-Ducanes, Sarah Lynne (Quezon City School of Economics, University of the Philippines Diliman, 2019)
Democracy has been seen to be under threat in light of President Duterte’s war on drugs regime. As such, it is imperative to look into what can restimulate democracy in the Philippines. Literature has pointed to voter turnout as a key indicator of democracy, and has pointed to campaign spending as in turn, a key determinant of voter turnout. Using ordinary least squares regression (OLS), this study explores the relationship between voter turnout and the campaign spending of the 2016 National Elections congressional candidates (aggregated at the city and municipal levels), integrating other explanatory variables that can impact voter turnout. An ordinary least squares (OLS) regression was used. The results indicate the existence of a positive and significant relationship between campaign spending and voter turnout.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendix.
Keywords: Campaign funds -- Philippines